Isolamento, cultivo e caracterização de células derivadas de cardioesferas de camundongos CD1 - Alves, Poliana Rodrigues (2013)
In Brazil, as in the world, cardiovascular diseases have been a major cause of death. The high mortality and few therapeutic alternatives for this disease have stimulated research on the stem cell field. Recently some groups have shown the presence of resident stem cells in the heart that can generate new cardiomyocytes. However, the cardiac stem cells exist in small amounts in vivo and their isolation and ex vivo expansion is a challenge for clinical use. In this study, our goal was to isolate, characterize and grow cardiosphere-derived cells from CD1 mice. Surface molecules present in these cells were analyzed by flow cytometry and expression of cytoplasmic proteins was analyzed by immunofluorescence. Primary cells were isolated from the hearts of adult mice after digestion of the organ into small pieces using 420U/ml of collagenase II in four cycles of 5 minutes at 37°C. Subsequently, cells were maintained in culture in an incubator at 37°C and 5% CO2 for approximately 3 weeks. The immunofluorescence assays and flow cytometry were performed between passages 3 and 5 which 0.25% trypsin was used. The cells expressed the following proteins in their cytoplasm: vimentin, desmin, nestin and α-smooth muscle actin and population doubling time was 1.8 days. Additionally, flow cytometry showed low expression of the molecules CD19 (0.4), CD45 (0.5) and CD90 (4.77), and higher expression of CD73 (71.47), CD105 (25.1), CD14 (25.17). These results suggest that the CDC isolated from CD1 mice are cells with a mesenchymal phenotype, but their beneficial potential in cardiac repair remains to be tested.